Evaluation of cornmercial soil mixtures for growing coffee (Coffea arabica L. var caturra) in nurseries. - Argueta, Flor de María; Rodríguez, Rocio; Monroig, Miguel (Agronomía Mesoamericana, 2016)
We evaluated five commercial mixtures against a control treatment consisting of a mixture of soil, sugar cane sludge and silt, which is commonly used in the production of coffee trees in nurseries. The cultivation of coffee trees in the mixture made of perlite, vermiculate and peat moss, was similar to that of plants grown in the control treatment. We detected significant differences in stem diameter and in the fresh weight of foliage. The nutritional analysis of the leaves showed significant differences in K, Mg and Mn contento The levels of the two last elements were significantly lower in the control treatment